Exposure to parental mortality and markers of morbidity, and the risks of attempted and completed suicide in offspring: an analysis of sensitive life periods. Issue 3 (5th October 2010) - Niederkrotenthaler, Thomas; Floderus, Birgitta; Alexanderson, Kristina; Rasmussen, Finn; Mittendorfer-Rutz, Ellenor
Abstract : Background: There is evidence of parental risk factors for suicidal behaviour in offspring, but research on variations in their effects with offspring's age at first exposure is sparse. Aims: To explore the effects of age at exposure to parental mortality and markers of morbidity on the risks of suicide and attempted suicide in offspring. Methods: This was a case–control study effected through record linkage between Swedish registers. Individuals born 1973–83 who committed suicide (n=1407) or were hospitalised due to an attempted suicide (n=17 159) were matched to ≤10 controls by sex, month and county of birth. ORs were measured in time windows representing age at first exposure. Results: A general pattern of increasing risks of suicide and attempted suicide in offspring with decreasing age at exposure to parental risk factors emerged. Adjusted suicide risk (OR (95% CI)) was most pronounced in the youngest exposure window for parental psychiatric disability pension (3.1 (1.6 to 5.8)), somatic disability pension (1.9 (1.0 to 3.4)), psychiatric inpatient care (2.5 (2.0 to 3.1)), parental attempted suicide (2.9 (2.0 to 4.1)) and suicide (2.9 (1.7 to 5.2)). For parental non-suicidal deaths, the general pattern was the opposite. Patterns in offspring attempted suicide were similar to completed suicide for parental disability pension, psychiatric inpatient care and non-suicidal death. Attempted suicide risk after parental suicide showed an increasing trend with increasing age at exposure. Conclusion: Parental morbidity and parental suicidal behaviour show the most detrimental effects on completed suicide among offspring when they appear early in life. Early interventions in families at risk are necessary to prevent suicide in offspring.